Knowledge audit adoption: A case study of Malaysian electricity supply industry - Drus S.M.; Shariff S.S.M.; Othman M. (International Business Information Management Association, IBIMA, 2023)
Economics; Electric utilities; Information management; Regional planning; Sustainable development; Electricity companies; Empirical data; Formal knowledge; Knowledge audits; Knowledge economy; Knowledge-intensive industries; Malaysia; Organisational knowledge; Industrial economics